Hubungan Kecemasan dengan Kualitas Tidur Pada Mahasiswa Tingkat Akhir - Tri Okta Ratnaningtyas; Dwi Fitriani (STIKes Kharisma Persada, 2020)
Students are one of the early adult groups who have a lot of activities, so that students become a group that is at risk of having poor sleep quality. One of the causes of poor sleep quality is anxiety factor. This research was conducted to identify the relationship between anxiety with sleep quality in the final level students at STIKes Kharisma Persada. The research design in this study used analytic observational research with a quantitative approach and cross sectional design, with sample was 133 respondents taken by using a simple random sampling. Data collection was performed using a questionnaire and data analysis used chi square statistical test. Based on the results of the research showed that most respondents were 21 years old, female, most respondents experience anxiety with mild levels of autonomic stimulation, mild muscle and bone effects, mild situational anxiety, and experiences in dealing with mild anxiety, have good sleep quality based on aspects of subjective sleep quality, sleep latency, sleep duration, sleep efficiency, sleep disorders, and the use of good sleeping pills and most of the respondents have sleep quality which is based on aspects of the disruption of activity. Based on the results of bivariate analysis with chi square test, it is known that there is a relationship between anxiety and sleep quality with p value = 0.014. There is a relationship between anxiety and sleep quality in final level students.